Flexible nanocomposites as conductive electrode materials - Ong, Wei Jun (2014)
Flexible nanocomposites may be an alternative to electrode applications. The common nanocomposites are polymer matrix nanocomposites with MWCNT or CNF as its filler. For the nanomaterial filler to display good electrical conductivity, a high quality dispersion method and good stabilization of the nanomaterial is required. Hence, in our study we compared between ball milling and manual milling dispersion method. We also compared between the electrical properties of MWCNT and CNF as the filler material. A suitable stabilization method for both of the nanomaterials must exist. In other studies, a common dispersant for both MWCNT and CNF was not reported yet. The other approaches for stabilization are either costly or complicated or resulted in lowered electrical conductivity. In our study, we conducted feasibility studies on the Chinese ink as dispersant for both MWCNT and CNF. Also, we fabricated electrodes from the nanocomposite solution using the freestanding method; we assembled the electrodes into a supercapacitor and conducted feasibility studies on the supercapacitor too. For the comparison of nanomaterials, MWCNT and CNF were added in varying concentrations in the composite solution with Chinese ink as the dispersant. The composite solution was then allowed to air dry for 72 hours to obtain the electrodes and the electrical conductivity was measured using four point probe resistivity measurement. To compare between ball and manual milling, the steps and measurements were mostly similar to the ones listed above expect that different milling methods were used. The air dried electrodes were assembled into supercapacitor, cyclic voltammetry and charge/discharge test were conducted on it. From our results, MWCNT could achieve up to 17.17 S/cm with 2 wt % of MWCNT loading while CNF could achieve up to 26.64 S/cm with 2.33 wt % of CNF loading. Ball milling was found to be more suitable for CNF whereas manual milling was more suitable for MWCNT. FE-SEM images indicated good dispersion of MWCNT and CNF in the composite when using Chinese ink as dispersant. Our specific capacitances could reach up to 73.48 mF/cm2 and 70.85 mF/cm2 for MWCNT and CNF respectively. It is evident that Chinese ink is a suitable dispersant for MWCNT and CNF. For future works, it is recommended that the person investigate on ball milling time for CNF. The person may also investigate on possibilities to reduce the air drying time and to increase the specific capacitance for the supercapacitor.